ORANG KALANG DI PULAU JAWA, TINJAUAN HISTORIS - Diman Suryanto (BRIN, 2003)
In various ancient Javanese inscriptions, a lot of kalang term is found, the meaning of which is often associated with the timber profession. This understanding comes from the reality of the existence of kalang people in the later days, namely a group of people who live in the forest in several places in Java as woodcutters.